2012
DOI: 10.1002/pc.22229
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide 6‐wheat straw composites: Degradation kinetics

Abstract: Degradation kinetics of ground wheat straw (WS), polyamide 6, and a WS‐polyamide 6 composites obtained from extrusion were investigated. 15 wt% of ground WS was melt blended with other additives naming; lithium chloride salt (LiCl) and N‐butylbenzenesulfonamide plasticizer (N‐BBSA) as matrix treatments. The additives were added to reduce the melting point of polyamide 6 and ease of composite processing (reduction in processing temperature and time). Two commonly used non‐isothermal kinetic models were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Reducing the melting point of polyamides is an effective method, and an increase in the number of papers indicates that small amounts of lithium chloride (LiCl) could decrease the melting point of PA6; then PA6 and wheat straws were blended together to prepare PA6/wheat straw composites. The results indicated that LiCl increased the tensile and flexural modulus, but decreased the impact strength, the tensile strength, and the flexural strength [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the melting point of polyamides is an effective method, and an increase in the number of papers indicates that small amounts of lithium chloride (LiCl) could decrease the melting point of PA6; then PA6 and wheat straws were blended together to prepare PA6/wheat straw composites. The results indicated that LiCl increased the tensile and flexural modulus, but decreased the impact strength, the tensile strength, and the flexural strength [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increment in degradation and decomposition temperature may be attributed to the removal of lignin and hemicellulose. [24,32] Figure 1D shows the surface morphology of extracted cellulose from wheat straw.…”
Section: Structural and Thermal Stabilitymentioning
confidence: 99%
“…For example, Herrera et al [22] showed values of 162, 91 and 164 kJmol -1 to PA6, PA66 and PA612, respectively (values in the range between 250-475 °C). Gu et al [14] obtained a E A of 197 kJmol -1 for a semi-aromatic polyamide containing benzoxazole at ≈ 425°C and Amintowlieh et al [23] obtained 201 kJmol -1 for a PA6 at 437 °C. These values are expected for non-aromatic PA and the variations among them are due to the variation of the crystalline degree and the concentration of amide groups per repetitive unit.…”
Section: Degradation Behaviormentioning
confidence: 99%